ENGINEERING-GEOPHYSICAL RESEARCHES FOR THE SELECTION OF WATER SUPPLY TUNNEL OPTIMAL ROUTE OF MEGHRI HPP (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The article considers the results of complex geophysical studies performed in the south of the republic due to the planned construction of the Meghri HPP. As a result, the necessary data for hydro-geological, geo-geological conditions of the site and possible tectonic faults were obtained, which will be used for the HPP construction.
Keywords: Meghri HPP; geophysical methods